The role of conflict, feedback, and action comprehension in monitoring of action errors: Evidence for internal and external routes. (June 2019) - Howard, Cortney M.; Smith, Louisa L.; Coslett, H. Branch; Buxbaum, Laurel J.
Abstract: The mechanisms and brain regions underlying error monitoring in complex action are poorly understood, yet errors and impaired error correction in these tasks are hallmarks of apraxia, a common disorder associated with left hemisphere stroke. Accounts of monitoring of language posit an internal route by which production planning or competition between candidate representations provide predictive signals that monitoring is required to prevent error, and an external route in which output is monitored using the comprehension system. Abnormal reliance on the external route has been associated with damage to brain regions critical for sensory-motor transformation and a pattern of gradual error 'clean-up' called conduite d'approche (CD) . Action pantomime data from 67 participants with left hemisphere stroke were consistent with versions of internal route theories positing that competition signals monitoring requirements. Support Vector Regression Lesion Symptom Mapping (SVR-LSM) showed that lesions in the inferior parietal, posterior temporal, and arcuate fasciculus/superior longitudinal fasciculus predicted action conduite d'approche, overlapping the regions previously observed in the language domain. A second experiment with 12 patients who produced substantial action CD assessed whether factors impacting the internal route (action production ability, competition) versus external route (vision of produced actions, action comprehension) influenced correction attempts. In these 'high CD' patients, vision of produced actions and integrity of gesture comprehension interacted to determine successful error correction, supporting external route theories. Viewed together, these and other data suggest that skilled actions are monitored both by an internal route in which conflict aids in detection and correction of errors during production planning, and an external route that detects mismatches between produced actions and stored knowledge of action appearance. The parallels between language and action monitoring mechanisms and neuroanatomical networks pave the way for further exploration of common and distinct processes across these domains. Graphical abstract: Image 1